2023
DOI: 10.1177/22799036231181852
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the user satisfaction on COVID-19 vaccination service in Indonesia

Abstract: Background: The implementation of the COVID-19 vaccination is still being carried out in Indonesia to enhance immunity against SARS Cov-2 infection. However, the information about vaccination service satisfaction is still very limited. This study aims to assess how satisfied Covid-19 vaccination service users are in Indonesia. Design and methods: This is an analytic study with a cross-sectional design was conducted through an online survey in the third week of June 2022. People with a minimum age of 17 years, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In addition, instead of using a single question to measure satisfaction, future studies should consider adopting a more in-depth survey instrument to measure satisfaction from multiple levels. For example, the SERVQUAL instrument is widely used in assessing health service satisfaction, which consists of five dimensions: tangibility, reliability, responsiveness, assurance, and empathy [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, instead of using a single question to measure satisfaction, future studies should consider adopting a more in-depth survey instrument to measure satisfaction from multiple levels. For example, the SERVQUAL instrument is widely used in assessing health service satisfaction, which consists of five dimensions: tangibility, reliability, responsiveness, assurance, and empathy [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Satisfaction, in the context of vaccine users, refers to their personal perceptions of how happy or satisfied they are with the vaccine service they received [ 11 ]. This is measured by the extent to which the participants are satisfied with their experiences of getting vaccinated.…”
Section: Introductionmentioning
confidence: 99%
“…Repeated unfulfilled promises regarding COVID-19 mitigation strategies may have eroded trust and willingness to follow new preventive behaviors, such as taking a booster dose [ 72 ]. A study found that the vaccination service itself divided society almost equally in terms of satisfaction and dissatisfaction [ 73 ]. In addition, the relatively lower severity of the Omicron variant among the younger age group [ 74 , 75 ] has contributed to a false sense of security, reducing the perceived threat of the virus.…”
Section: Background and Key Issues Of The Covid-19 Pandemic In Indonesiamentioning
confidence: 99%